2001
DOI: 10.1039/b009705p
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and preconcentration of vanadium(v) and vanadium(iv) in water samples by flow injection-inductively coupled plasma optical emission spectrometry and ultrasonic nebulization

Abstract: An on-line separation, preconcentration and determination system for vanadium(IV) and vanadium(V) comprising inductively coupled plasma optical emission spectrometry (ICP-OES) coupled to a flow injection (FI) method with an ultrasonic nebulization (USN) system was studied. The vanadium species were retained on an Amberlite XAD-7 resin as a vanadium-2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (V-5-Br-PADAP) complex at pH 3.7. Enhanced selectivity was obtained with the combined use of the formation on-line of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 30 publications
3
35
1
Order By: Relevance
“…For this purpose chelating resins 11-14 and several modified polymers [15][16][17] have usually been applied. Determination of vanadium at trace levels is important for monitoring pollution as well as for understanding its geochemical and biological effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose chelating resins 11-14 and several modified polymers [15][16][17] have usually been applied. Determination of vanadium at trace levels is important for monitoring pollution as well as for understanding its geochemical and biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, the whole preconcentration step was very slow (2 and 4 h for a batch and column procedure, respectively). Wuilloud et al 15 reported a sensitivity enhancement of 225 in determination of vanadium by ICP-OES after its preconcentration on an Amberlite XAD-7 resin as a vanadium-2-(5-bromo-2-pyridylazo)-5-diethylaminophenol complex. However, the enrichment factor that resulted from the application of microcolumn was only 15.…”
mentioning
confidence: 99%
“…After the species have been separated by any of these techniques, they are quantified by UV [14,17], chemiluminescence [27], ICP [28], or ICPMS [14].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Catalytic spectrophotometry 12-14 is a conventional method used for determination of vanadium with high sensitivity, but generally this kind of method can not distinguish the vanadium species. Recently, a solid phase extraction (SPE) and detection procedures for preconcentration and separation of trace analysis have been developed, using ionexchange resins, 15,16 chelating resins, 17,18 chelating functional group, 19 chelating agents, 20 and activated carbon, 21 coupled with fluorination assisted electrothermal vaporization (FETV)-ICP-OES, 15 FIA-ICP-OES, 16 ICP-AES, 19 electrothermal atomic absorption spectrometry (ETAAS) 22 and graphite furnace AAS. 18,21 However, many of these methods are expensive, timeconsuming, and reagent-consuming; they require skillful operators and must be performed in batchwise.…”
Section: Introductionmentioning
confidence: 99%